2010
DOI: 10.1177/0363546509361190
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Upper Extremity Injuries Sustained by Falling During Snowboarding

Abstract: Two snowboarding stances as well as 2 falling directions had a significant influence on the frequency of the injured side in the upper extremity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Davidson et al 14 reported that the difference in the number of injuries for the leading and trailing legs was present for both knee and ankle injuries, but was only significant for knee injuries. For upper extremity injuries, there was no correlation between the affected side and the leading leg,14 or whether the rider has a regular or goofy stance,35 but rather the injured side was related to the direction of falling 19 35. There is currently no explanation in the literature as to why the leading leg appears to be much more vulnerable compared with the trailing leg.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Davidson et al 14 reported that the difference in the number of injuries for the leading and trailing legs was present for both knee and ankle injuries, but was only significant for knee injuries. For upper extremity injuries, there was no correlation between the affected side and the leading leg,14 or whether the rider has a regular or goofy stance,35 but rather the injured side was related to the direction of falling 19 35. There is currently no explanation in the literature as to why the leading leg appears to be much more vulnerable compared with the trailing leg.…”
Section: Methodsmentioning
confidence: 99%
“…In surveys that encompass all snowboarders, an average of 50% identified themselves as ‘novice’ or ‘beginner’, 37% as ‘intermediate’ and 13% as ‘advanced’ 2 4 5 16 25 29 35 46. The majority of participants in snowboarding are described as beginners who have had little to no professional instruction2 25 46; consequently, this group experiences a large share of the injuries 8 11 19 21 25 35 47.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence and pattern of injury have been identified to differ between snowboarders by varying ability (Bladin et al 2004;Yamauchi et al 2010). Beginners with less than 5 days snowboarding experience are more prone to injury, due to the numerous falls involved in learning this new skill (Rønning et al, 2001;Langran and Selvaraj, 2004).…”
Section: Risk Groupsmentioning
confidence: 99%